Potenciais de desenvolvimento em um sistema local de inovação: uma análise do município de Engenheiro Coelho - SP - Panaino, Robertson Campelo (Universidade Federal de São Carlos, 2019)
This research aims to analyze the activities, find the potentialities and relationships in the Local Innovation System (LIS) of a small municipality. Innovation is essential as a competitive factor in companies, yet other organizations and institutions within an Innovation System (IS) can assist in this process. In general, IS can be understood as all factors that contribute in some way to technological development, in addition to the dispersion and use of innovation, whether economic, social, institutional, organizational, political, among others. The government has been moving to develop and mature LISs, with laws, incentives, technology parks, among others. For this purpose, the municipality of Engenheiro Coelho in the interior of the state of São Paulo was selected, which is close to important economic and innovation centers, but with indicators much lower than most of the cities in its region. The theory was based on the concepts of location-based ISs (national, state and local / municipal), as well as the classification of an IS according to its activities and relationships between agents. From the theory emerged the variables used to analyze the Engenheiro Coelho LIS. Through a qualitative approach, interviews were conducted and later the content analysis using WebQDA analysis software, as well as a document analysis. From the analysis pointed out the potential of this LIS to develop innovative activities and strengthen relationships between agents. Using these results, public, business and academic managers will be able to make improvements in LIS with a view to its maturation. The conclusions point to some immaturity in the studied LIS, proposing a series of actions to promote its development, besides pointing out the main innovation agents present in Engenheiro Coelho / SP.
Development potentials in a local innovation system: an analysis of the city of Engenheiro Coelho - SP
Keywords: Inovação; Sistema Local de Inovação; Cooperação Universidade-Empresa; Innovation; Immature Local Innovation Systems; University-industry cooperation; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO